El buen humor como virtud en la práctica docente (2017)
Objective and textual typology. The “Ethics and leadership” course, part of the curriculum of the PhD in Education, gives origin to the concern for analyzing the relationship between good humor –a moral virtue, treated by Aristotle- and teaching. Due to the positive association between good humor and learning –as evidenced by research- the objective of this article shows a reflection on the importance of this virtue in educational practice.Methodology. From a hermeneutic-dialectic vision, we seek to explain the meaning of good humor in the classroom and the importance of positive ethics of humor to promote both moral and intellectual virtues. Several studies presented by Jáuregui and Fernández (2009), Perandones, Lledó and Herrera (2013), Morreall (2010, 2014) and Siruana (2013) have linked sense of humor to the reduction of anxiety, to positive mood and as a promoter of other virtues, which has given guidelines to ensure that humor should be an integral part of any educational methodology.One of the basic functions of good humor is to be a form of social communication and to be connected to the code of social culture. Further investigation of this virtue in the classroom can strengthen motivation and promote a climate of harmony and cooperation.Results. Humor in teaching practice requires good judgment, many hours of work and experience. Research has shown the positive value of good humor associating it with the strengthening of intrapersonal and interpersonal relationships and as an engine for the development and consolidation of other virtues, which shows that there can be no education without ethics and that man is humanized through the virtues.